2022
DOI: 10.1556/2006.2022.00065
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of problematic pornography use among help-seeking male adolescents: Latent profile and network analysis

Abstract: Background and aims Little data exist on exploring the subgroups and characteristics of problematic pornography use (PPU) in help-seeking adolescents. The aims of the study were to classify the subgroups among help-seeking male adolescents, explore their similarities and differences, and uncover their core symptoms. Methods A total of 3,468 Chinese male adolescents (M age = 16.64 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 105 publications
(152 reference statements)
0
10
0
Order By: Relevance
“…According to our scoping review, withdrawal symptoms may represent core symptoms of PPU 27–29 . These findings, although preliminary, may represent an argument in favor of understanding PPU within the addiction framework 16,17,41 .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…According to our scoping review, withdrawal symptoms may represent core symptoms of PPU 27–29 . These findings, although preliminary, may represent an argument in favor of understanding PPU within the addiction framework 16,17,41 .…”
Section: Discussionmentioning
confidence: 61%
“…Studies based on the Problematic Pornography Consumption Scale (PPCS-18) or the short version of the Problematic Pornography Consumption Scale (PPCS-6) 27–29 described that the items assessing withdrawal symptoms were considered central symptoms of PPU in their samples. In addition, one of these studies 28 described that participants who were considering treatment for their pornography use reported significantly higher scores in the withdrawal symptoms item of the PPCS-6 in comparison with the not-considering treatment group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, one of the potential reasons for the stronger association in this study compared to previous work [ 18 ] might relate to the different cultural context where the samples were recruited. Most studies reported that Chinese people’s attitude toward sex is more conservative [ 70 ], and they are more likely to experience guilty and conflicted as using pornography [ 71 ]. Therefore, when the participants with high levels of ADHD symptoms used pornography to cope with their stressful situations, they may be inclined to think that they have used “too much”, and then scored higher in BPS.…”
Section: Discussionmentioning
confidence: 99%
“…A significant p value ( p < .05) indicates that a model with more classes is appropriate. However, the p value is sensitive to sample size; therefore, the p value can remain nonsignificant in larger samples (Bőthe et al, 2020; Jiang et al, 2022). Based on the classification derived from the LPA, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV), and accuracy for PUTS cutoff scores were reported (Altman & Bland, 1994a, 1994b; Glaros & Kline, 1988).…”
Section: Methodsmentioning
confidence: 99%